Intended and unintended effects of restrictions on the sale of cigarillos to youth: evidence from Canada. Issue 4 (7th March 2014) - Nguyen, Hai V; Grootendorst, Paul
Abstract : Background: Youth consumption of cigarillos (ie, little cigars) has increased markedly in recent years. In July 2010, the Canadian government banned the sale of flavoured cigarillos and required unflavoured cigarillos to be sold in packs of at least 20 units. This paper assesses changes in young persons' use of cigarillos and regular cigars, which are potential substitutes, following the policy. Methods: To investigate of the change in cigar smoking following the policy, we constructed a segmented regression model that allowed the policy to change the height and the slope of the trend in the outcome variables. The model was estimated using data from the 2007–2011 Canadian Tobacco Use Monitoring Surveys. Results: We obtained visual and regression-based evidence that use of cigarillos among youth declined following the policy. We also found a small, gradual increase in their use of regular cigars, possibly due to their compensatory switching from cigarillos to regular cigars. Overall, there was a net reduction in cigar use among youth after the intervention. Interpretation: The policy achieved its goal of reducing youth's consumption of cigarillos, but may have an unintended consequence of increasing their use of regular cigars. Policymakers should address the possibility that youth switch to regular cigars in response to restricted access to cigarillos. Possible ways of discouraging this substituting behaviour include extending the ban to cover all flavoured cigars and mandating a minimum pack size for all cigars, or raising taxes on flavoured cigars.